A Narrative Review on Therapeutic Potential and Efficacy of Medhya Rasayana - Neha Mehra; Shailendra Pradhan; D.C. Singh (AYUSHDHARA, 2023)
Anything that imbalance body and mind is known to cause disease. Nowadays, mental health has been becoming a global threat to the world. Ayurveda has a novel concept of Rasayana. Medhya Rasayana that has been classified under Rasayana for the stability of Dhi, Dhriti, Smriti. The action of Medhya Rasayana is explained with the help of using neurons and neurotransmitters in modern neurophysiology. Information is gathered from various Nighantus, Samhitas, other Ayurvedic textbooks and various online sources such as Google scholar, Sci-hub, Science Direct etc. Medhya Rasayana has a very good anti-oxidant, adaptogenic, anabolic, anti-stress and anti-depressant property. This literature review article is about the four medicinal plants such as Mandukaparni (Centella asiatica Linn.), Yasthi madhu (Glycyrrhiza glabra Linn.), Guduchi (Tinospora cordifolia (Willd.) Hook. F. and Thomas.), Sankhpushpi (Convolvulus pluricaulis Chois) which are most common Medhya Rasayana mentioned in Ayurvedic samhitas, Nighantus etc.